Approaches for Spatholobus littoralis: Comparative Efficiency of Ultrasound- and Microwave-Assisted Extraction Techniques and Its Statistical Analysis - Muliawati, Nindya Tri; Sholeha, Novia Amalia; Ramdhan, Mohamad Alief; Laila, Farida; Sujarnoko, Tekad Urip Pambudi; Yulianti, Wina; Supardan, Atep Dian; Resmeiliana, Ika; Listiasari, Faranita Ratih; Muthmainna, Hanifa; Fadillah, Khaerunisa; Akbar, Muhammad Afdhal Maliki (Hydrogen: Jurnal Kependidikan Kimia, 2026)
The rising demand for sustainable bioactive materials has expedited the advancement of green extraction technologies sourced from renewable natural resources. This research systematically evaluates Microwave-Assisted Extraction (MAE) and Ultrasound-Assisted Extraction (UAE) for the recovery of bioactive compounds from Spatholobus littoralis Hassk (bajakah root) utilising ethanol. The extraction performance was assessed based on yield, total phenolic content, and physicochemical characteristics. The findings indicated that MAE exhibited superior extraction efficiency and enhanced physicochemical properties relative to UAE. The biological functionality of the extracts was assessed using an anti-termite assay. Bajakah root extracts, derived through MAE, were evaluated at concentrations of 1.5% and 2.5%. A commercial termiticide (Permise®) served as a positive control, while 70% ethanol acted as a solvent control, and untreated samples were designated as a negative control. The anti-termite assay demonstrated that both extract concentrations resulted in complete termite mortality within 2 days, while the positive control took up to 5 days and the untreated group required up to 7 days. The findings indicate the efficacy of S. littoralis root extract as a natural bioactive agent and underscore MAE as a reliable and sustainable extraction method for the advancement of multifunctional green materials.